Tantangan Dan Solusi Dalam Implementasi Kurikulum Merdeka Pada Pembelajaran PAI Bagi Anak Berkebutuhan Khusus Di SD Darul Fathonah Kudus - Dian Rusydianti; Abdul Hakim Majid; Muhammad Nur Latif; Moh. Solihuddin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) for students with special needs (ABK) is a strategic issue in realizing inclusive and equitable education. This study aims to identify the challenges and formulate solutions for implementing the Merdeka Curriculum in PAI learning at SD Darul Fathonah Kudus, an inclusive school. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The findings reveal several key challenges, including the limited competence of teachers in inclusive pedagogy, lack of adaptive learning resources and media, learning gaps among students with different diagnoses, and inadequate disability-friendly facilities. These results highlight the urgency of continuous teacher training, the development of responsive instructional media, and systemic support from schools and policymakers. This research contributes to the strengthening of contextual and humanistic models of Islamic education within inclusive settings. The implications call for synergy among practitioners, academics, and stakeholders, and suggest further exploration through multi-site studies and data triangulation to deepen understanding of PAI learning dynamics for students with special needs.